Guide de la banque pour tous. Innovations africaines - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1998)
Banques populaires, villageoises ou solidaires, caisses locales, caisses d'épargne et de crédit servent déj